APLIKASI SETORAN PARKIR BERBASIS PROGRESSIVE WEB APPLICATION DENGAN NOTIFIKASI WHATSAPP GATEWAY - Purwanto, Hari Lugis (Department of System Information, 2025)
Parking deposit management often encounters obstacles ranging from deposit discipline to transaction recording. Field conditions show that parking attendants frequently delay the deposit process, especially during unfavorable weather, while treasurers face time constraints as they work during the same hours as the attendants, making them often unavailable. The limited devices owned by parking attendants also pose a challenge, as their smartphones can only run lightweight applications and are restricted to basic browsing and communication via WhatsApp. These conditions demand a technological solution that is flexible, easy to use, and does not burden the devices used by attendants. The purpose of this study is to implement a Progressive Web Application (PWA) with WhatsApp gateway notifications to support parking deposit reporting. PWA enables web applications to function like mobile applications but with minimal resources and fast access. The results of this study successfully developed a web-based parking deposit application by applying PWA, transforming the web-based deposit program into a mobile-like application that simplifies user access. Users no longer need to type URL addresses through the browser. Furthermore, the implementation of WhatsApp messages or notifications allows real-time communication, while receipt delivery becomes easier and does not consume smartphone storage space since receipts are sent in the form of links.